Agency in advanced liberal services: grounding sociological knowledge in homeless people's accounts - Parsell, Cameron (The British journal of sociology, 2019)
This paper aims to understand how people who are homeless respond to advanced liberal social services that endeavour to promote their autonomy and responsible actions. We prioritize the experiences and positions of people who are homeless, and what agentic action means to them. Sociological literature is selective about what accounts are deemed agentic. Agency is associated with accounts that resist or subvert dominant neoliberal framings of homelessness as failure of individuals. When people experiencing homelessness or poverty themselves foreground autonomy or responsibility, sociologists treat them as cultural dopes who have internalized neoliberal discourse. Our analysis is driven by an ethnographic study in an Australian homelessness shelter. We demonstrate how people who are homeless neither outright reject nor completely embrace advanced liberal practices to influence their actions and promote autonomy. People engaged in relational reasoning. Paternalist and advanced liberal social services were both lauded and rejected for their capacities and limitations to realize a good life. We contribute to the discussion for sociology to value people's accounts and experiences, rather than broader social process explaining their accounts. From the perspectives of people who are homeless, we show that just because something appears neoliberal does not mean it should be automatically rejected.